Identification of a growth-inhibitory epitope in PfRipr5, a malaria vaccine candidate against Plasmodium falciparum - Nagaoka, Hikaru; Fukushima, Akihisa; Tsuboi, Takafumi; Takashima, Eizo (Frontiers in Immunology, 2026)
BackgroundThe Plasmodium falciparum Rh5-interacting protein (PfRipr) is a key component of the pentameric PTRAMP-CSS-PfRipr-CyRPA-RH5 (PCRCR) complex, which is essential for erythrocyte invasion. Antibodies against PfRipr can inhibit parasite growth, but the full-length protein is structurally complex and challenging to produce as a recombinant antigen. We previously found that a specific PfRipr fragment, PfRipr5, was the most potent antigen; however, identifying minimal functional regions within PfRipr5 is critical for improving the vaccine design.MethodsWe investigated PfRipr5, a truncated fragment of PfRipr consisting of EGF-like domains 5–9, and identified the epitope recognized by the growth-inhibitory monoclonal antibody 29B11. Epitope characterization was conducted using Western blotting with cysteine-substituted mutants and surface plasmon resonance (SPR) analysis with a single-site kinetics model.Results and conclusionThe identified 20-amino-acid region represents a cysteine-associated epitope recognized by the growth-inhibitory monoclonal antibody 29B11. This study defines a growth-inhibitory epitope within PfRipr5 whose recognition is associated with cysteine integrity. These findings provide a tractable molecular entry point for dissecting PfRipr function and support epitope-focused strategies for rational design of subunit vaccines against blood-stage malaria.